Children and families in health and illness - Broome, Marion; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1998)
This book synthesizes the nursing research literature in the health promotion of children, pediatric acute and chronic conditions, and children and families in the health care system. Professionals and researchers will find this book helpful.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pediatric nursing; Family nursing; Pediatric nursing -- Research; Family nursing -- Research; Electronic books